Performance of a Small-sized Savonious Blade with Wind Concentrator - Dygku. Asmanissa Awg. Osman; Norzanah Rosmin; Aede Hatib Mustaamal; Siti Maherah Hussin; Md Pauzi Abdullah (Institute of Advanced Engineering and Science, 2018)
This paper presents the performance of a fabricated small-sized Savonious wind turbine with two blades. The design of Savonius vertical axis wind turbine (VAWT) was based on Malaysia wind speed condition. Meanwhile, the design of wind concentrator was based on the dimensions and the constant airflow of an air compressor. From the experimental testing in a laboratory, it was found that the proposed Savonious turbine has best performance when tested using wind concentrator. To conclude, airflow from air compressor can be increased when the proposed wind concentrator is used and hence increasing the proposed VAWT performance in terms of its angular speed (ω), tip speed ratio (TSR) and the generated electrical power (PE).